Revitalisasi Pendidikan Politik Melalui Pembentukan Kampung Anti Money Politic - Marsudi, Kenlies Era Rosalina; Sunarso, Sunarso (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
This paper aims to find a resolution in overcoming the phenomenon of the rise of money politics that occurs before general elections in Indonesia. With the decline of money politics in the run-up to the general election, it will automatically reduce the number of corruption, collusion and nepotism which are still high and can attract competent and trustworthy leaders and representatives in carrying out their duties as servants of the people. By conducting qualitative descriptive research, researchers collect data and explore the real conditions that exist in society regarding the money politics phenomenon and try to find the right solution. The establishment of anti-money politics villages in several villages in Yogyakarta is a recent breakthrough as political education in rural communities which has been shown to be able to reduce the number of money politics drastically in the lead up to general elections. Political education through the establishment of anti-money politics villages can increase the understanding and political awareness of the public even though the community resources are still low. Other regions in Indonesia that are prone to money politics need to emulate the application of anti-money politics village as the latest political education model to realize good democracy in Indonesia.